The Specific Anatomical Morphology of Lateral Ankle Ligament: Qualitative and Quantitative Cadaveric based Study - Chirapat Inchai; Tanawat Vaseenon; Yasuhito Tanaka; Pasuk Mahakkanukrauh (Orthopaedic Surgery, 2023)
Objective The accurate understanding in morphological features of the lateral ankle ligaments is necessary for the diagnosis and management of ankle instability and other ankle problems. The purpose of this study was to evaluate the anatomical morphology and the attachment areas of lateral ligament complex of ankle joint based on the cadaveric study. Methods Fifty‐four fresh frozen cadaveric ankles were dissected to evaluate the lateral ankle ligaments. Each ligament was separated into two or three small bundles. In the investigated footprint areas, acrylic colors were used as a marker point to locate specific areas of ligament bundle attached to the bone. The Image J software was used to measure and analyze the sizes of the specific footprint areas to achieve descriptive statistical analysis. Results The double bands of anterior talofibular ligament (ATFL) were found as a major type in the present study with 57.41% (31 of 54 ankles) while the single band of ATFL was observed in 42.59% (23 of 54 ankles). The attachment sizes of the ATFL, posterior talofibular ligament (PTFL) and calcaneofibular ligament (CFL) were evaluated into two areas; proximal and distal attachments. The average of proximal or fibular part of ATFL, PTFL and CFL were 85.06, 134.27, 93.91 mm2 respectively. The average of distal part of ATFL, PTFL and CFL were 100.07, 277.61, 249.39 mm2 respectively. Conclusion Considering the lateral ankle ligament repaired or reconstruction especially using arthroscopy, the precise understanding in specific detail of the lateral ankle ligament may help both diagnose and select the appropriate treatment for solving the ankle problems. These observations may help the surgeon to perform the surgical procedure for determining the appropriate techniques and avoid complication to patients.